Membangun Manajemen Daerah Perbatasan yang Efektif - Khairul Muluk (JIANA ( Jurnal Ilmu Administrasi Negara ), 2010)
The main problem of this research is ineffectiveness of border area management. Toomany problems are faced by field administrator and local authority which is raised by lack ofinstitutional support from central and local government. New model of border area managementis needed in strengthening its effectiveness. This model was arranged by considering empiricalresult such as different function of multilevel government, lack of coordination and incapableinstitutional arrangement, and lack of management effectiveness. This study based on descrip-tive qualitative methods. Informan is choiced with purposive and collecting data used snowballing method the new model propose that there must be a clear division of authority betweencentral, provincial and local government through principle of externality, effectiveness and effi-ciency. This new model entails proper institutional design that strengthening coordination be-tween multilevel government and empowering institutional design in local authority.